Natural environment satisfaction moderates the protective effect of legal cognition on adolescent aggression - Fan, Lu; Chen, Yan; Zou, Xuee; Xu, Shuhui (Frontiers in Psychology, 2025)
Adolescent aggression poses a threat to community wellbeing and sustainable crime prevention. Grounded in situational crime prevention and social control theories, this study examined whether legal cognition (understanding of legal norms and rights) predicts lower aggression and whether natural environment satisfaction moderates this effect. In spring 2024, 518 adolescents (12–22 years) in Zhejiang Province completed validated scales of legal cognition, aggression, and environmental satisfaction. Hierarchical regression and PROCESS Model 1 analyses showed that legal cognition negatively predicted aggression (β = −0.34, p < 0.001) and that environmental satisfaction also inversely related to aggression (β = −0.30, p < 0.001). Critically, the legal cognition × environment interaction explained an additional 4.5% of aggression variance (ΔR2 = 0.045, p = 0.002), with the buffering effect of legal cognition being strongest at high environmental satisfaction. These results suggest that combining legal-norm education with enhancements to natural settings (e.g., increased green space, reduced pollution) may offer a scalable strategy for adolescent violence prevention.